Enhancing the Renewable Energy and GDP Share of Agriculture in Indonesia: Analysis of the Impacts on Agricultural Sector Employment - Hilmy Prilliadi (İzmir İktisat Dergisi)
Renewable energy capacity, agricultural sector GDP, and agricultural employment in Indonesia experienced a downward trend from 1990 to 2019. This trend negatively impacts Indonesia’s target to utilize renewable energy as its energy source, employment in the agricultural sector, and the importance of agriculture to the Indonesian economy. Based on these issues, this research examined the impact of renewable energy usage and agricultural sector GDP on the employment rate of the agricultural sector by implementing the Autoregressive Distributed Lag (ARDL) model. According to empirical findings, total renewable energy supply improves agricultural sector employment in the short and long run; however, agricultural sector GDP improves employment only in the short run and negatively impacts the long run. It suggests that renewable energy has the potency to enhance agricultural employment. The use of renewable energy is expected to be a solution for the decrease in employment in the agricultural sector along with the GDP decrease. Governments can make sure that all funds allocated to an agroecological program or policy are used to increase agricultural renewable energy use. Renewable energy regulations should be assessed based on their ability to reduce pollution while also ensuring a reliable energy supply for the agricultural sector at an affordable price.